Unveiling systemic responses in kidney transplantation: interplay between the allograft transcriptome and serum proteins - Buscher, Konrad; Rixen, Rebecca; Schütz, Paula; Van Marck, Veerle; Heitplatz, Barbara; Gabriels, Gert; Jehn, Ulrich; Braun, Daniela Anne; Pavenstädt, Hermann; Reuter, Stefan (Frontiers in Immunology, 2024)
Immunity, as defined by systems biology, encompasses a holistic response throughout the body, characterized by intricate connections with various tissues and compartments. However, this concept has been rarely explored in kidney transplantation. In this proof of concept study we investigated a direct association between the allograft phenotype and serum protein signatures. Time-matched samples of graft biopsies and blood serum were collected in a heterogenous cohort of kidney transplanted patients (n=15) for bulk RNA sequencing and proteomics, respectively. RNA transcripts exhibit distinct and reproducible co-regulated gene networks with specific functional profiles. We measured 159 serum proteins and investigated correlations with gene expression networks. Two opposing axesone related to metabolism and the other to inflammation -were identified. They may represent a biological continuum between the allograft and the serum, and correlate with allograft function, but not with interstitial fibrosis or proteinuria. For signature validation we used two independent proteomic datasets (n=21). Our findings establish a biological link between the allograft transcriptome and the blood serum proteome, highlighting systemic immune effects in kidney transplantation and offering a promising framework for developing allograft-linked biomarkers.